Management of in-feed antibiotics for swine: evaluation of alternative dietary strategies - Resende, Maíra (2021)
Two experiments were conducted to evaluate the effects of the replacement (partial or complete) of antibiotics (ANT) by nutritional additives for pigs in the nursery to finishing phase. The objective of study 1 was to evaluate the effects of benzoic acid (BA) and essential oils (EO) on cellular and humoral immune response, morphology, gene expression, antioxidant capacity in the jejunal mucosa, and cecal content microbiota in weaned piglets and growth performance from the nursery to finishing phase. One hundred and twenty barrows were weaned and assigned in a randomized block design: basal diet (BD) without additives (NC), BD with ANT (PC), and BD with 0.3% BA and EO (BA+EO). In the nursery phase, the PC piglets showed a greater body weight (BW) and average daily gain (ADG), and a lower feed conversion ratio (FCR) compared to the NC group, but similar levels to the BA+EO group. In the growing phase, the PC treatment resulted in a greater BW and average daily feed intake (ADFI), and in the finishing phase the BW of the BA+EO group was similar to that of the PC group and greater than that of the NC group. In the total period, the BW and ADG of the PC and BA+EO pigs were similar and higher than those for the NC treatment. The BA+EO pigs had the lowest incidence of diarrhea during the nursery period. The use of BA+EO reduced the counts of total white blood cells (WBC) and neutrophils. In the microbiome analyses, it was observed that the BA+EO and PC groups had similar cecal microbiota when compared to the NC piglets. A significant increase in the number of operational taxonomic units (OTUs) was observed in the BA+EO group. In conclusion, supplementation with BA+EO reduced the inflammatory response and modified the cecal microbiome in the post-weaning period, resulting in an improvement in the growth performance of finishing pigs. The objective of study 2 was to evaluate the use of yeast products (YP) and EO in total or partial replacement to the in-feed antibiotic protocols (growth promoter and prophylactic), both in recommended doses and in overdose of prophylactic antibiotics, on growth performance, diarrhea incidence in the growing-finishing pigs, and fecal microbiota in market hogs. Four hundred pigs (20.36 ± 2.64 kg) were assigned in a randomized block design: diets with prophylactic and growth promoter antibiotics (ANT); ANT with 30% more prophylactic antibiotics (ANT+30); diets with less prophylactic antibiotics and YP (ANT+Y); diets with less prophylactic antibiotics, YP and EO (ANT+Y+EO); and diets free antibiotics and with YP and EO (Y+EO). From 0 to 14d, pigs of the ANT+30, ANT+Y, and ANT+Y+EO treatments showed a greater BW and ADG compared to pigs from the Y+EO group. From 14 to 35d, pigs of ANT+30 and ANT+Y+EO treatments were to be heavier than Y+EO group. At 105d, ANT pigs had a higher BW than the Y+EO group. For the entire period, ADG of ANT pigs were greater and FCR better than Y+EO pigs. From 49 to 70d, ANT+Y and ANT+Y+EO treatments showed a lower diarrhea incidence than Y+EO group, which remained the case during the overall period. At 105d, the alpha diversity of fecal microbiota were lower in ANT+30 and Y+EO groups than observed for ANT+Y+EO group. In conclusion, the use of YP and EO (growth promoter and prophylactic), in partial replacement to the in-feed antibiotic protocols, does not reduce the growth performance, can replace antibiotic growth promotors, and reduce the in-feed use of prophylactic antibiotics in growing-finishing pigs. The use of YP and EO, together with prophylactic antibiotics, increase the microbial diversity, despite having important genera for weight gain in less abundance. Overdose of prophylactic antibiotics does not improve growth performance and reduces microbial diversity, which does not characterize it as an efficient preventive protocol.